Physico-Chemical Properties of Pigment in Garden Pansy (Viola × Wittrockiana Gams.) (Bangladesh Journal of Botany, 2022)
Pansy is a good potential resource for natural pigments due to its rich flower colours. In the present study, pigment from a pansy breeding line, E01, was extracted and its solubility in different reagents and stability under various environmental conditions were investigated. The pigment extracted displayed watersoluble property and was also dissolved in acid (HCl) and alkaline (NaOH) reagents and relatively polar solvents, but insoluble in nonpolar solvents. The pigment-water solution had an absorbance peak at 238 nm with amaranthine colour under acidic conditions. It was stable in aqueous solution under normal conditions. However, it was easily spoiled when exposed to high pH (> 4), high temperature (> 80℃) or under intense light exceeding 170000 lx. The stability of pigment was significantly influenced by Cu2+, but scarcely affected by Na+, Mg2+ and Ca2+. These results will be helpful for commercial prospects of pansy pigment in natural food colour industry.Bangladesh J. Bot. 51(3): 433-438, 2022 (September)